A Study on the Characteristics of Substrate Metabolism Changes in Mild Cognitive Impairment Elderly During Acute Novel Modified Qigong Exercise (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract:Research Purpose:This study aimed to investigate the substrate metabolism changes in elderly individuals with mild cognitive impairment during acute exercise of a novel modified Qigong (KKQ) at Khon Kaen University (KKU) in Thailand. The study utilized indirect calorimetry to measure the changes in substrate metabolism indicators of elderly individuals with cognitive impairment after a single acute Qigong exercise. The effects of KKU Qigong exercise on the rates of fat oxidation and carbohydrate oxidation were analyzed, and the potential metabolic effects of Qigong practice in elderly individuals with cognitive impairment were explored. The research aims to provide scientific guidance for exercise training in elderly individuals with mild cognitive impairment and to support the promotion and development of the novel modified Qigong at Khon Kaen University, contributing to the advancement of this Qigong practice through scientific research.Research Method:A total of 60 participants (66.07 ± 4.28 years old) were recruited for the study and randomly divided into two groups: the KKU Qigong Group (KQG) and the Control Group (CG). Prior to the experiment, all participants underwent a physical health assessment to ensure they did not have any significant health issues and were suitable for KKU Qigong exercise. All participants received verbal instructions and signed informed consent forms. The Montreal Cognitive Assessment (MoCA) was used to assess cognitive function, with a total score of 30 points, and a score of 26 or above was considered normal. Participants with scores below 26 were identified as having mild cognitive impairment and selected for the study. After screening, the KQG group consisted of 22 participants, and the CG group consisted of 23 participants.In the KQG group, participants wore a respiratory gas analysis device (Oxycon mobile V-707270 SBx, Germany) during a 30-minute KKU Qigong exercise session, while the CG group engaged in 30 minutes of sedentary reading. Data were collected before the Qigong exercise, during the exercise (30 minutes), and during a 30-minute recovery period after the exercise. Parameters measured included oxygen uptake (VO2), carbon dioxide output (VCO2), respiratory exchange ratio (RER), and heart rate (beats per minute). Energy expenditure indices (energy expenditure rate, total energy expenditure) and substrate metabolism indices (carbohydrate oxidation rate, fat oxidation rate, energy substrate contribution ratio, and consumption) were calculated and compared between the two groups. The data were analyzed using repeated measures analysis of variance (ANOVA).Research Results:1. In this study, the heart rate during continuous KKU Qigong exercise was as follows: 5 minutes (104.24±23.24 beats/min), 10 minutes (103.40±19.55 beats/min), 15 minutes (99.58±14.65 beats/min), 20 minutes (99.38±14.03 beats/min), 25 minutes (102.82±18.98 beats/min), 30 minutes (102.67±18.61 beats/min), and 5 minutes during recovery (91.28±12.95 beats/min). Previous research has defined heart rates below 119 beats/min as low-intensity and 120-149 beats/min as moderate-intensity. The heart rate range during KKU Qigong exercise was 92.4 beats/min to 107.8 beats/min, indicating that KKU Qigong belongs to low-intensity exercise.2. The impact of KKU Qigong exercise on substrate metabolism in elderly individuals with cognitive impairment: Fat oxidation rate (g/min) showed an initial increase followed by a decrease during KKU Qigong exercise, and the differences between the KKU Qigong Group (KQG) and the Control Group (CG) were significant at 5 minutes, 10 minutes, and 5 minutes during recovery (P<0.05). Carbohydrate oxidation rate (g/min) remained higher in KQG compared to CG throughout the KKU Qigong exercise, and significant differences were observed between the two groups during the 5-30 minutes of exercise (P<0.05). RER data in KQG decreased initially and then increased during the exercise. At the start of KKU Qigong exercise, the RER value was 0.88, indicating a predominant reliance on fat oxidation for energy supply during the initial phase of low-intensity exercise. As the exercise progressed, the RER value gradually increased, approaching 1.0, signifying a shift towards greater reliance on carbohydrate oxidation for energy supply, with a relative decline in fat oxidation rate.3. The KKU Qigong exercise was performed twice consecutively during the 30-minute exercise session. The study found that the fat oxidation rate during the second Qigong exercise was significantly lower than during the first exercise. This was attributed to the fact that the body was in an already activated state during the first exercise, while during the second consecutive exercise, the body's metabolic state tended to stabilize, leading to a lower energy expenditure during the second exercise.4. Within the KKU Qigong Group, significant differences were observed in Fat oxidation rate (g/min) and Carbohydrate oxidation rate (g/min) during the 30-minute KKU Qigong exercise, except for the baseline data (P<0.05). This indicates that during low-intensity aerobic Qigong exercise, the body primarily relies on aerobic metabolism for energy supply. In the acute 30-minute Qigong exercise, the fat oxidation rate may be relatively high due to the low exercise intensity, but the carbohydrate oxidation rate is even higher. This results in a larger proportion of carbohydrates in substrate utilization. This suggests that elderly individuals with cognitive impairment tend to utilize carbohydrates as their primary energy source during acute Qigong exercise.Research Conclusion:1. KKU Qigong belongs to low-intensity aerobic exercise.2. During the 30-minute acute KKU Qigong exercise, the fat oxidation rate was faster in the first exercise session compared to the second exercise session. This finding may be attributed to the body's better adaptation to the exercise during the first session. This discovery provides valuable clues for further investigating the long-term effects and training adaptability of Qigong practice.3. In the acute 30-minute low-intensity KKU Qigong exercise, the carbohydrate oxidation rate was higher than the fat oxidation rate, indicating that carbohydrates can more efficiently provide energy, making them suitable for meeting the energy demands of low-intensity and short-duration exercises. The body adjusts substrate utilization according to exercise intensity and duration to meet different energy demands.4. Acute exercise of the novel modified Qigong has significant effects on substrate metabolism in elderly individuals with mild cognitive impairment. Qigong practice significantly increases carbohydrate oxidation rate, while the fat oxidation rate is relatively less affected. This suggests that Qigong exercise may have positive effects on the body's metabolism in elderly individuals with cognitive impairment, providing a potential non-pharmacological intervention approach for cognitive impairment management and prevention.